The Design of a Gamified Responsible Use of Social Media - Marcial, Dave E.; dela Peña, Lawrence; Montemayor, Jade; Dy, Joy (Frontiers in Education, 2021)
Social media is part of almost everyone’s daily life. Its networking facilities redefines the way people connect and interact with each other. However, social media is reported being misused in different ways, especially the millennials. There is a need to elevate the teens' level of empowerment on the responsible use of social media. Other technological innovations like augmented reality (AR) and digital gamification provides pedagogical benefits. Digital gamification in the classroom is a teaching strategy that translates content and delivery into a game using digital technology. On the other hand, AR is an emerging technology to enlarge real-life situations in multimedia. Research shows both technologies increase interactivity well as attention span among the learners. Additionally, these technologies, including social media, are among the many useful tools in teaching 21st-century learners once correctly used. With this, a game-based mobile application was developed to advocate responsible use of social media among teens. The learning content was gamified in augmented reality to provide an innovative teaching and learning way at Silliman University. This paper describes the gamification design of the learning trail on the topic of responsible use of social media. Specifically, it presents the publishing process of the augmented reality mobile application about responsible use of social media. Kuhlmann’s 3C Model (Challenge, Choices, Consequences) was utilized to formulate the learning content. It also demonstrates the design phases, game mechanics and the general evaluation of the learning application. Four challenges were developed. These are a) be familiar with security and privacy policies, b) do not express concerns about others, even if you think you are anonymous, c) respond to digital offenders, d) do not tell the world about an upcoming vacation. These challenges were translated into graphics and animations. The animated material was compiled, programmed, and published to a server of the mobile application. The gamified learning trail on responsible use of social media is accessible through QR codes leading to the augmented reality interface. The design was validated and found to be relevant and engaging.